Design mobile user interface (MUI) prototype for mobile learning application in secondary school / Affaf Yusof - Yusof, Affaf (Faculty of Computer and Mathematical Sciences, 2007)
This project is focus on how to design mobile user interfaces (MUI) for mobile learning application. This topic was chosen because the area of mobile user interface is still evolving. This project used the "overview + detail" visualization technique to design the mobile user interface (MUI) and finally implement some of this ideas in a prototype and tested it. The guidelines give several rules that should be followed when designing an interface to make sure that it is efficiency, easy to use and flexible to meet the user's satisfaction. Some of the guidelines are the interface should be consistent, support leamability, reversal of action, use familiar terms, good error prevention and many more. In designing the interface for mobile device, there are also some limitations and problems the designers will face. The major problems in designing an interface for mobile device are limited memory or capacity and the small screen size compared to desktop. Due to these problems, there are also the solutions included in this report.